2013
DOI: 10.1128/aac.01366-12
|View full text |Cite
|
Sign up to set email alerts
|

Caspofungin Kills Candida albicans by Causing both Cellular Apoptosis and Necrosis

Abstract: Caspofungin exerts candidacidal activity by inhibiting cell wall (1,3)-␤-D-glucan synthesis. We investigated the physiologic mechanisms of caspofungin-induced Candida albicans cell death. Apoptosis (programmed cell death) and necrosis were studied after C. albicans SC5314 cells were exposed to caspofungin at 0.06, 0.125, and 0.5 g/ml (0.5؋, 1؋, and 4؋ the MIC, respectively) for 3 h. Caspofungin at 0.125 and 0.5 g/ml reduced cellular viability by >50%, as measured by colony counts and methylene blue exclusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
132
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(147 citation statements)
references
References 39 publications
8
132
0
Order By: Relevance
“…However, when conditions are more favorable they can revert to a state of colony-forming competence [38]. It is possible that C. albicans cells exposed to ascorbate in PBS without shaking may have moved toward a state of 'early apoptosis' as there was no overt loss of viability by CFU determination, but only a delayed formation of colonies [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, when conditions are more favorable they can revert to a state of colony-forming competence [38]. It is possible that C. albicans cells exposed to ascorbate in PBS without shaking may have moved toward a state of 'early apoptosis' as there was no overt loss of viability by CFU determination, but only a delayed formation of colonies [39].…”
Section: Discussionmentioning
confidence: 99%
“…Metacaspase activation, a distinct biochemical marker of apoptosis, has been previously characterized in Saccharomyces cerevisiae and C. albicans. 16,19,23 Recently, other research groups have demonstrated metacaspasedependent apoptosis in planktonic and sessile cells of C. albicans. [23][24][25] In conclusion, we provide evidence that MICA triggers apoptotic features in C. albicans and C. parapsilosis biofilms including in CAS-NS strains.…”
Section: Discussionmentioning
confidence: 99%
“…17 Biofilms pretreated with MICA (0.25-4.0 mg/mL) for 3 h at 37 C were fixed with 3.7% formaldehyde for 30 min on ice and were digested with a lysing enzyme mixture (0.25 mg/ mL of chitinase, 15 U of lyticase, and 20 mg/mL lysing enzyme; Sigma-Aldrich) for 3 h at 30 C. The enzyme-digested cells were used to detect DNA fragmentation by means of the TUNEL assay as previously described. 16 The cells were observed for fluorescence as described above, with excitation and emission wavelengths of 488 nm and 520 nm, respectively.…”
Section: Mitochondrial Membrane Potential Measurements In Candida Biomentioning
confidence: 99%
See 1 more Smart Citation
“…of Candida albicans [28]. The substance may be toxic as well for host cells and for host mitochondria [29].…”
mentioning
confidence: 99%